EDUCATIONAL COURCES MODERNIZATION: METHOD OF EFFICENCY EVALUATION - Vasilii M. Kartvelishvili; Eduard A. Lebedyuk (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article presents the methodological and methodical foundations of research on the current state of adaptation of the educational programs in higher education institutions to modern requirements of scientific and technical progress. A software system was developed to solve the task of the uniqueness analysis of a documents corpus. Furthermore, it can be applied for the analysis of the effectiveness of educational programs modernization by comparing the calculated uniqueness of documents and accompanying meta information. Using developed software based on InterSystems Caché platform and iKnow, authors conducted analysis of the educational programs corpus in the field of information technology. The possibility of applying author's methodology in the related fields, particularly in the field of research of the viability of educational process in the University is shown.